A Correlational-Comparative Study of Burmese High School Students’ Motivation and Academic Achievement in English as a Foreign Language Class - Mu, Bu; Orlando González (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The purpose of this quantitative study was to determine whether there was a significant relationship between motivation for learning English as a foreign language (EFL) and English academic achievement, and a significant difference in motivation for learning EFL, in terms of motivational intensity, desire to learn English, and attitudes toward learning English, between Grades 10 and 11 students at Mungmyit Sinli IDPs High School, Kachin State, Myanmar. A total of 225 students participated in this study. Motivation-related data were gathered through administering a survey questionnaire adapted from the international version of Gardner’s (2010) Attitude/Motivation Test Battery, while the English students’ monthly test scores were considered to measure participants’ English academic achievement. From the statistical analysis of the collected data, it was found that there was no significant relationship between Grade 10 students’ motivational intensity and desire to learn for learning EFL with their English academic achievement, while their attitudes toward learning English were found to have a significantly weak relationship with their English academic achievement. On the other hand, the results revealed that there was no significant relationship between Grade 11 students’ motivational intensity, desire to learn English and attitudes toward learning English with their English academic achievement. Besides, it was also found that there was a significant difference in motivational intensity between Grade 10 and Grade 11 students, while no significant difference was found in their desire to learn English and attitudes toward learning English. Based on these findings, recommendations for teachers, students, school administrators and future researchers are provided.